Unified strategy for nickel-catalyzed C-2 Alkylation of indoles through chelation assistance - Soni, Vineeta; Jagtap, Rahul A.; Gonnade, Rajesh G.; Punji, Benudhar (ACS Catalysis, 2016)
A nickel-catalyzed direct C-2 alkylation of indoles through monodentate-chelation assistance has been described. This reaction proceeds via an unusual strategy by the use of a well-designed and defined (quinolinyl)amido–nickel catalyst, [{κN,κN,κN-Et2NCH2C(O)(μ-N)C9H6N}Ni(OAc)], providing a solution to the limitations associated with bidentate-chelate auxiliaries. The method allows coupling of indoles with various unactivated primary and secondary alkyl halides with ample substrate scope. This uniquely strategized alkylation proceeded through crucial C–H activation and via an alkyl radical intermediate. The reaction by this approach represents a rare example of Ni-catalyzed monodentate-chelate-assisted C–H functionalization.

Unified approach to fused and spirocyclic oxindoles through lewis-acid-promoted opening of spiroepoxyoxindoles with allylsilanes: application to the formal synthesis of (+/-)-physovenine - Sharma, Brijesh M.; Yadav, Mahesh; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2017)
A protocol for the construction of oxindoles containing all-carbon quaternary centres in a highly regioselective manner has been developed. The reaction involves opening of spiroepoxyoxindoles with allylsilanes to give Hosomi-Sakurai-type products as well as new silicon-containing spirocyclic oxindoles. A formal synthesis of (+/-)-physovenine was accomplished in five steps using this protocol.
Keywords: alkaloids; Allylation; annulation; Lewis acids; spiro compounds

Unprecedented solvent induced inter-conversion between monomeric and dimeric silylene-zinc iodide adducts - Yadav, Sandeep; Sangtani, Ekta; Dhawan, Diksha; Gonnade, Rajesh G.; Ghosh, Debashree; Sen, Sakya S. (Dalton Transaction, 2017)
<div class="block-record-info" style="margin: 0px 22px 22px; list-style: none; padding: 0px; line-height: 20px; font-size: 13px; color: rgb(51, 51, 51); font-family: arial, helvetica, sans-serif; background-color: rgb(248, 248, 248);"> Usually, when a silylene reacts with a transition metal Lewis acid, it forms an adduct which could be either monomeric or dimeric. However, we present here that a silylene, [PhC(NtBu)(2)SiN(SiMe3)(2)] can form both monomeric [PhC(NtBu)(2)Si{N(SiMe3)(2)} -> ZnI2]center dot THF (1) and dimeric [{PhC(NtBu)(2)}(N(SiMe3)(2))SiZnI,(mu-I)](2) (2) adducts upon reaction with ZnI2. The formation of 1 and 2 relies upon the solvent used for the reaction or crystallization. When the crystallization is carried out in THF complex 1 is formed, however, when the reaction and crystallization are performed in acetonitrile complex 2 is obtained. Both 1 and 2 were structurally authenticated and the nature of the Si-Zn bond in these complexes was determined by quantum chemical calculations. In addition, a spontaneous inter-conversion between 1 and 2 just by changing the solvents has been also observed; a feature presently not known for silylene-transition metal Lewis adducts.
Keywords: Bis(Silylene ); Carbene Complexes; Crystal -structure Determination; Dative bond; Lewis acid base reaction; Ligands; Main- group compounds; Reactivity; Silicon(II) Bis(Trimethylsilyl)Amide; Carbonyl-Complexes

Unravelling the nucleophilicity of buten tides for 1,6-conjugate addition to p-quinone methides: a direct access to diversely substituted butenolide-derived diarylmethanes - Sharma, Brijesh M.; Shinde, Dinesh R.; Jain, Ruchi; Begari, Eeshwaraiah; Satbhaiya, Shruti; Gonnade, Rajesh G.; Kumar, Pradeep (Organic Letters, 2018)
A Lewis acid catalyzed regioselective C-C bond is constructed through beta-addition of deconjugated butenolides with p-quinone methides in a 1,6-conjugate addition manner. Interestingly, Lewis acid catalyzed vinylogous Mukaiyama-Michael reaction of silyloxyfurans with p-QMs proceeds selectively through the alpha or gamma position exclusively. The reaction is mild with broad substrate scope, thus allowing easy access to a wide range of bis-arylated alpha-/beta-/gamma-substituted butenolides.

Unsymmetrical sp(2)-sp(3) disilenes - Bisai, Milan Kumar; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2021)
Disilenes with differently coordinated silicon atoms are not known. Here, we have shown the high yield synthesis of a range of disilenes (2-4 and 6) upon reaction of a hypersilyl silylene PhC(NtBu)(2)SiSi(SiMe3)(3) (1) with aliphatic chlorophosphines. The most striking characteristic of these disilenes is the presence of two differently coordinated Si atoms (one is three-coordinated, the other four-coordinated). The analogous reaction with Ph2PCl did not afford the desired disilene, but, surprisingly, led to the first tetraphosphinosilane (8). DFT calculations were performed to understand the bonding in disilenes and differences in reactivity of the complexes.
Keywords: chlorophosphine; DFT; disilene; hypersilylsilylene

Uncovering diverse reactivity of NHCs withdiazoalkane: C-H activation, C=C bond formation,and access to N-heterocyclic methylenehydrazine - Balayan, Kajal; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Science, 2024)
N-heterocyclic carbenes (NHCs) have attracted significant attention due to their strong sigma-donating capabilities, as well as their transition-metal-like reactivity towards small molecules. However, their interaction with diazoalkanes remains understudied. In this manuscript, we explore the reactivity of a series of stable carbenes, encompassing a wide range of electronic properties, with Me3SiCHN2. 5-SIPr activates the C-H bond of Me3SiCHN2, resulting in the formation of a novel diazo derivative (1), while carbenes such as 5-IPr, 6-SIPr, and diamido carbene yield N-heterocyclic methylenehydrazine derivatives (3, 4, and 8). The reaction of Me3SiCHN2 with 5-ItBu unexpectedly leads to the formation of a triazole ring linked with the imidazole moiety via a CC double bond (6) alongside the azine product (7). Substituting the diazoalkane with diazoester consistently yields azine derivatives (9-12 and 14). Only in the case of 5-ItBu, an imidazolium salt with tetrazenide anion (13) was obtained as a side product. The reaction of 4 with HCl resulted in the desilylprotonation to form a salt, 5a, which undergoes deprotonation upon using bases such as Et3N and KHMDS to form N-heterocyclic methylene hydrazine, 5. Theoretical calculations have been conducted to elucidate the diverse mechanisms underlying product formation.

Unravelling polymorphism-driven luminescence in GFP chromophore analogues: insights into the phase transition and morphology-dependent optical waveguide properties - Dabke, Niteen B.; Raut, Yash; Mali, Bhupendra P.; Pandya, Rinu; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Journal of Materials Chemistry C, 2024)
The advent of multi-emission organic solid-state materials in response to external stimuli has sparked the scientific community due to their potential application in developing sophisticated optoelectronic sensors and bioanalytical tools. This article presents green fluorescent protein chromophore (GFPc) analogue-based polymorphs exhibiting significantly different emissions due to various noncovalent interactions in the supramolecular environment and conformational alterations in the crystalline state. In both compounds (A and B), the polymorphs undergo monotropic thermal phase transitions that are characterized by DSC, HSM, and VT-PXRD techniques. The distinct fluorescent emission characteristics of these polymorphs demonstrated morphology-related optical waveguiding features. Specifically, the plate-type Form A1 emitted light with a 2D blue hue, while the needle-type Form A2 emitted light with a yellowish-green colour. Additionally, the impressive waveguiding capabilities of Form B1 were explored in both straight and singly/doubly bending configurations to facilitate fluorescence propagation. Consequently, there is significant interest in developing organic materials based on GFP chromophores, which exhibit low emission in solution but display multi-fluorescent emission in the solid state. These materials are promising for applications such as optoelectronic devices, security tags, live cell imaging, and fluorescent inks. Polymorphs of GFPc analogs A and B display differences in their optical waveguiding properties in 1D and 2D depending on the crystal shapes. Furthermore, Form B1 demonstrates efficient optical waveguiding capabilities even when the crystal is bent.

Unified photoredox-catalyzed aerobic oxidative dynamic kinetic asymmetric transformation for C-N atropoisomers mediated by chiral organophosphites - Saikia, Pinku; Aarthika, M.; Bhattacharjya, Ayantika; Maity, Susmita; Bajpai, Priyam; Bera, Asish; Saha, Arindam; Gonnade, Rajesh G.; Vanka, Kumar; Maity, Pradip (Organic Letters, 2025)
The synthesis of anilides with a chiral C(=O)-N axis has relied on direct installation of the chiral C(sp2)-N(sp2) bond or enantioselective modification of the peripheral groups. However, these methods are constrained by the size and type of functional groups compatible with each strategy. Herein, we report a dynamic kinetic asymmetric transformation (DYKAT) for the aerobic oxidation of iminium ions to access C(=O)-N axial chirality that addresses those limitations. Furthermore, it eliminates the need for any auxiliary functional groups, which enables us to develop a unified method for the synthesis of atroposelective isoquinolone, lactam, and amide.